Plasma and genetic determinants of soluble TREM-1 and major adverse cardiovascular events in a prospective cohort of acute myocardial infarction patients. Results from the FAST-MI 2010 study. (1st December 2021) - Ait-Oufella, Hafid; Yu, Mengyao; Kotti, Salma; Georges, Adrien; Vandestienne, Marie; Joffre, Jeremie; Roubille, François; Angoulvant, Denis; Santos-Zas, Icia; Tedgui, Alain; Gibot, Sébastien; Derive, Marc; et al.
Abstract: Introduction: Triggering receptor expressing on myeloid cells (TREM)-1 is involved in the pathophysiology of ischemic heart disease. Plasma soluble TREM-1 levels (sTREM-1) has been associated with increased risk of major adverse cardiovascular events (MACE) in acute myocardial infarction (AMI) patients. However, the causative link between TREM-1 and MACE remains unknown and requires further investigation before developing potential therapeutic approaches. Methods and results: Using the serum and DNA data bank from the prospective, nationwide French registry of Acute ST-elevation and non-ST-elevation Myocardial Infarction (FAST-MI 2010, N = 1293), we studied the association of plasma levels of sTREM-1 with 9 common genetic variants at the TREM1 locus and their relationship with recurrent MACE over a 3-year follow up. Plasma levels of sTREM-1 were associated with an increased risk of MACEs (death, recurrent MI or stroke) (adjusted HR = 1.86, 95%CI = 1.06–3.26 and HR = 1.11, 95%CI = 0.61–2.02 respectively for tertiles 3 and 2 versus tertile 1, P < 0.001). The study of common variants identified two major genetic determinants of sTREM-1 (rs4714449: beta = −0.11, Padd = 7.85 × 10 −5 and rs3804276: beta = 0.18, Padd = 2.65 × 10 −11 ) with a potential role on maintenance and/or differentiation of hematopoietic stem cells. However, associated variants only explained 4% of sTREM-1 variance ( P = 2.74 × 10 −14 ). Moreover, the rs4714449 variant, individually and in haplotype, was not significantly associated with MACE (HR = 0.61, 95%CI: 0.35–1.05, P = 0.07). Conclusions: Despite its relationship with increased risk of death, recurrent MI and stroke, genetic determinants of plasma levels of sTREM-1 were not found to be causal prognostic factors in patients with acute myocardial infarction. Highlights: TREM-1 engagement activates myeloid cells and worsens cardiac remodeling in experimental acute myocardial infarction (AMI). High plasma levels of soluble TREM-1 associate with higher risk of recurrent major adverse cardiac events in AMI patients. Common TREM1 genetic variants are associated with sTREM-1 levels in AMI patients and explain 4% of its total variance. Further studies on MI patients are needed to assess the relationship between TREM1 genetic variants and outcome.